Effect of Hysterectomy on Ovarian Reserve in the Early Postoperative Period Based on the Type of Surgery - Chun, Sungwook (J Menopausal Med, 2020)
OBJECTIVES: This study aimed to evaluate the influence of simple hysterectomy on the ovarian reserve based on the type of surgery. METHODS: Eighty-six premenopausal women between 31 and 48 years who underwent hysterectomy for benign gynecologic disease without additional adnexal surgery at a university hospital participated in this study. Seventy-one patients underwent laparoscopy-assisted vaginal hysterectomy (LAVH), and 15 patients underwent abdominal hysterectomy (AH). Blood samples were obtained from all study participants on preoperative day and 3 days after the operation to determine the anti-Müllerian hormone (AMH) levels. RESULTS: The postoperative reduction of the mean serum AMH level in the LAVH group (0.42 ± 0.76 ng/mL) was greater than that in the AH group, although the difference was not statistically significant (0.01 ± 0.60 ng/mL) (P = 0.053). The mean baseline AMH level (2.59 ± 2.33 ng/mL) was significantly reduced to 2.24 ± 2.08 ng/mL at 3 days after hysterectomy, and the mean rate of decline of AMH levels after surgery was 13.61% ± 30.81%. In subgroup analysis based on the type of surgery, the mean serum AMH level decreased significantly after surgery in the LAVH group, but no significant changes were found in serum AMH levels before and after the surgery in the AH group. CONCLUSIONS: These preliminary results suggest that simple hysterectomy affects the early postoperative decline of ovarian reserve, and these results might vary depending on the type of surgery.